Pollution by Heavy Metals: Environmental Implications and Key Strategies for Remediation | Poluição por metais pesados: implicações ambientais e estratégias-chave para remediação - Fabrício Ângelo Gabriel; Emmanuelle Maria Gonçalves Lorena; Ana Paula Xavier de Gondra Bezerra; Ítala Gabriela Sobral Santos; Alex Souza Moraes; Fernando Cartaxo Rolim Neto (Revista Geama, 2016)
Heavy metals in  small amounts found in nature, are essential to the survival of animals and plants on the planet. However, is becoming worring the direct and indirect releases of the heavy metals in the environment, causing negative effects and the imbalance in the cycle of these chemicals. This activity is progressive increase in the face of population growth, agriculture and industrial sectors, the main dispersers of this pollutant for the production of goods and services. The influence of these environmental contaminants is considerably wide and can be found in air, water, soil and consequently in food, passing the necessary conditions for an ecological imbalance. The arrangement of these metals in nature affects, often irreversibly, the ecosystem as a whole, resulting in short- or long-term risk of living organisms and human health. This review reports the contamination caused by different heavy metals and their potential to cause damage to fauna, flora and humans. Thus, in order to minimize the impacts, it is necessary to highlight the problems about polluting activities as a subsidy for concentration of efforts in the development of innovative and sustainable methods for remediation.